DETERMINATION OF THE ESSENCE AND STRUCTURAL ELEMENTS OF THE ECONOMIC POTENTIAL OF THE REGION - DONCHAK, LESYA; SHKVARUK, DINA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article substantiates the importance of such concepts as "potential" and "economic potential", which are the main basis for the effective functioning of any country, region or enterprise and formed its own vision of these categories. which can be used in the process of achieving current or future goals. With regard to the category of "economic potential of the region", it is advisable to consider all economic resources, opportunities, capabilities of the territorial unit to carry out economic and production activities, meet public needs, use all possible components of the region for economic, social and economic growth. The main structural components of the economic potential of the region are characterized, which include environmental potential, financial, resource, human resources, quality of life potential, investment and innovation potential. Thus, the concept of "economic potential of the region" includes not only a set of resources, but also the qualitative characteristics of the regional systems themselves. These characteristics allow us to assess the orientation of the existing system of industrial relations, development priorities, social policy in the regions to address the challenges of modernization. Based on the study, the close relationship between the main structural elements of economic potential has been proven. Thus, the economic potential of the region is a complex, dynamic system that depends on the best combination of certain types of economic resources, opportunities, abilities that are involved in the production process and affect the level of efficiency of its management. And this is the sum of all the potentials of the region, and their optimal use to identify the economic base of the object of study. Thus, the study shows that the use of economic potential should always be associated with the achievement of certain goals and improve the economic development of the territorial unit or the country as a whole.